Improving asset information management and the quality of construction projects in South Africa using building information modelling - Maphosa, Yolanda Skhululiwe (Stellenbosch : Stellenbosch University, 2025)
Maphosa, Y. S. 2025. Improving Asset Information Management and the Quality of Construction Projects in South Africa Using Building Information Modelling. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/b92e76cc-01b3-483c-9f5c-060d7c7d33e7